Computer Assisted Language Instruction: AI-based English Teaching to English For Sciences Students - Ahmed Sardi; Syarifuddin Dollah; Abdullah Abdullah (Universitas Islam Negeri Palopo, 2025)
This study aims to explore the perceptions and experiences of science students in using artificial intelligence (AI) technology as an assistive medium in learning English. The research adopts a descriptive qualitative approach, conducted at STKIP Darud Da’wah Wal Irsyad (DDI) Pinrang. The study participants consist of eight students from various science study programs who have used AI applications such as Grammarly, ChatGPT, and Duolingo as part of their learning process. Data were collected through in-depth interviews, observation, and documentation, and then analyzed thematically using Braun & Clarke’s approach. The findings indicate that AI serves as an adaptive learning facilitator, enhances learning autonomy, and promotes the development of writing and speaking skills in English. Students expressed positive responses towards AI due to its ability to provide instant feedback and personalization features. However, challenges were also identified, including AI’s limitations in understanding specific scientific terms and technical obstacles related to interface and internet connectivity. This study concludes that AI is effective as a learning companion for English language acquisition among science students, but its use needs to be supported by curriculum integration and continuous lecturer guidance.